Pembinaan Perilaku Dan Sosial Masyarakat Dalam Spirit Berqurban Didesa Kelebuk - Milhan; M. Maliki Oktama; Rizki Fajar; Ali Ambar; Fahrudin MZ, Irawan; Susilawati (Jurnal Pengabdian, 2025)
This article discusses collaborative community service activities between lecturers from the Business Management Department and the Business Law Department of the Junjungan State Sharia Institute (ISNJ) Bengkalis on Strengthening Understanding from the Perspective of the Qur'an and Hadith. The purpose of this community service is to provide an understanding of sacrifice to the community based on the Qur'an and Hadith located in Kelebuk Village, Bengkalis District, Bengkalis Regency. The methods used in this community service are lectures, questions and answers, and discussions. The orientation of this activity includes empowering the community to overcome the problems they face, meaning that they themselves will become actors in the era of globalization and rapid social change, where social behavior faces various challenges and complex dynamics. Fostering social behavior in the community is an important aspect in creating a harmonious, productive, and effective community. Good social behavior not only contributes to social stability, but also to individual and collective well-being in society.